On the opportunity of β-radiation detection by SI detectors in the Chernobyl failure area - Kulibaba, V.I.; Mazilov, A.A.; Maslov, N.I. (Вопросы атомной науки и техники, 2006)
It is demonstrated that a double silicon detector operating in the coincidence mode [1,2] can be used in radiationmonitoring instruments for registering β-radiation at high γ-background conditions, e.g., in Chernobyl.